2019
DOI: 10.1002/cssc.201802681
|View full text |Cite
|
Sign up to set email alerts
|

Highly Porous Hypercrosslinked Polymers Derived from Biobased Molecules

Abstract: FredrikB jçrnerbäck andN iklas Hedin* [a] Highly porousa nd hyper-cross-linked polymers (HCPs) have a range of applications and are typicallys ynthesized in an unsustainable manner.H erein, HCPs were synthesized from abundant biobased or biorelatedc ompounds in sulfolane with iron(III) chloride as Lewis acid catalyst. As reactants, quercetin, tannic acid, phenol, 1,4-dimethoxybenzene, glucose, and a commercial bark extract wereu sed. The HCPs had high CO 2 uptake (up to 3.94 mmol g À1 at 0 8Ca nd 1bar), tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…This indicated that -CH 2 CH 2crosslinks were also formed in the externally crosslinked HCP. The presence of newly formed crosslinking methylene bridges in these HCPs was also validated with 13 C-NMR.…”
Section: Chemical Structures Of Ow-produced Hcpsmentioning
confidence: 89%
See 4 more Smart Citations
“…This indicated that -CH 2 CH 2crosslinks were also formed in the externally crosslinked HCP. The presence of newly formed crosslinking methylene bridges in these HCPs was also validated with 13 C-NMR.…”
Section: Chemical Structures Of Ow-produced Hcpsmentioning
confidence: 89%
“…This was achieved with an ATR-FTIR (Nicolet iS10 with Smart iTX Diamond accessory, Thermo Fisher Scientic, Waltham, MA) with 64 scans per sample and a resolution of 0.48 cm −1 . The chemical structures of the synthesised HCPs were validated with solid-state 13 C cross polarisation (CP) magic angle spinning (MAS) nuclear magnetic resonance (NMR) spectroscopy using a Bruker Avance III spectrometer with a 9.4 T superconducting magnet.…”
Section: Characterisationmentioning
confidence: 99%
See 3 more Smart Citations